Non-canonical Kinases and Substrates in Cancer Progression - Vega, Francisco M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a printed edition of the Special Issue "Non-canonical Kinases and Substrates in Cancer Progression" that was published in the scientific journal Cancers. It was edited by Francisco M. Vega, Ph.D. from the University of Seville in Spain. It brings together the latest views and original research on non-canonical protein kinases, substrates, and scaffolds